Functional Restoration of a Midforearm Level Amputation using the Second Toe Transfer - Mohit Sharma; K. S. Shravan Rai; G. Srilekha Reddy; Shruti Kongara (Indian Journal of Plastic Surgery)
Unilateral midforearm level amputation is a severely debilitating situation. The present solution for this problem is either restoration of function using a prosthetic hand, or a vascularized composite allotransplant (VCA) in some very selected cases. In cases of distal forearm level amputations, even vascularized second toe transfer could be done on the radial side of the hand to achieve good functional restoration. We present a case of midforearm level amputation in which the second toe transfer has been done above the level of insertion of pronator teres muscle to achieve meaningful function. This report highlights the fact that a single toe transfer could be helpful in achieving meaningful prehension, even at this proximal.